Hambatan Guru Bahasa Indonesia dalam Pelaksanaan Pembelajaran pada Masa Pandemi di SMPN 01 Siak Hulu - Nita, Adha April; Mukhlis, Muhammad (UIR PRESS, 2021)
This research is entitled Barriers of Indonesian Language Teachers to the Implementation of Learning Stages During the Pandemic Period at SMPN 01 Siak Hulu. This study uses a qualitative research design that aims to describe the obstacles Indonesian language teachers have in implementing the learning stages during the pandemic at SMPN 01 Siak Hulu. The subject of this research is the Indonesian language teacher. The object of this research is the teacher's problem in implementing the stages of Indonesian language learning, namely Initial Activities, Core Activities, and Closing Activities. The data collection method used, namely the interview and documentation method. The problem in the implementation of learning is that in the preliminary activities the teacher does not carry out context building activities for students. The results obtained in the initial activities of teachers are still constrained in providing motivation, one of which is communication. In the core learning activities, the teacher does not use the media as a tool in the implementation of learning, and the stages of scientific learning are not carried out properly. The problem at the end of the learning activity is that the teacher does not evaluate directly after the lesson ends. Suggestions that can be given in this study are that teachers are expected to increase their knowledge and abilities in implementing learning systems, both face-to-face and online learning systems or using available applications.